2010
DOI: 10.3109/01421590903473969
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational games on medical students’ learning outcomes: A systematic review: BEME Guide No 14

Abstract: The available evidence to date neither confirm nor refute the utility of educational games as an effective teaching strategy for medical students. There is a need for additional and better-designed studies to assess the effectiveness of these games and this article will inform this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 31 publications
3
153
0
4
Order By: Relevance
“…Pero además, Weisskirch (2006) sostiene que los pasatiempos pueden servir como herramientas para que los estudiantes puedan medir el grado de comprensión sobre algún tópico particular, a modo de guía de autoevaluación, que les permitirá tener una noción "a la carta" de la comprensión e incorporación de dichos contenidos, lo cual promueve aún más la participación activa de los estudiantes en el proceso de enseñanza-aprendizaje. El beneficio del uso de pasatiempos educativos como herramientas didácticas en el proceso de enseñanza-aprendizaje ha sido evidenciado por numerosos autores (Childers, 1996;Silberman, 1996;McKeachie, 2002;Franklin et al, 2003;Lewis, 2003;Castañeda, 2005;Weisskirch, 2006;Olivares et al, 2008;Akl et al, 2010).…”
Section: Introductionunclassified
“…Pero además, Weisskirch (2006) sostiene que los pasatiempos pueden servir como herramientas para que los estudiantes puedan medir el grado de comprensión sobre algún tópico particular, a modo de guía de autoevaluación, que les permitirá tener una noción "a la carta" de la comprensión e incorporación de dichos contenidos, lo cual promueve aún más la participación activa de los estudiantes en el proceso de enseñanza-aprendizaje. El beneficio del uso de pasatiempos educativos como herramientas didácticas en el proceso de enseñanza-aprendizaje ha sido evidenciado por numerosos autores (Childers, 1996;Silberman, 1996;McKeachie, 2002;Franklin et al, 2003;Lewis, 2003;Castañeda, 2005;Weisskirch, 2006;Olivares et al, 2008;Akl et al, 2010).…”
Section: Introductionunclassified
“…However, further objective assessment of the use of all types of electronic media in medical education is needed before widespread adoption can be justified [13,14]. Specifically, it is unclear whethertheimprovedinterestandsatisfactionseenwithelectronic educational content translates to improved learning and material retention.Thereislimiteddatacomparinggame-basedteachingto didactic lectures withrespect to information retention andconcept understanding, and the few studies performed have shown conflicting results [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This increases the risk of skill loss during this retention period and thus may lead to lower transfer. This risk counts especially for procedural tasks that must be practiced often to acquire routine ( Van Merrienboer & Kirschner, 2007 (Akl et al, 2010).…”
Section: Type Of Tasksmentioning
confidence: 99%